(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this article, we provid a number of Hermite-Hadamard type fractional integral inequalities for the Atangana-Baleanu and Prabhakar fractional operators, using extended generalized Mittag-Leffler functions as their kernel. Significant findings are provided for the integral inequalities involving fractional integrals of the type (_1 +, _2 -) and (_1 + _2 2). By employing certain functions to create visual graphs with matching numerical entries that depict the inequalities, we show the veracity of our findings.